Spar platform at deep water region in Malaysian sea - Saiful Islam, A.B.M.; Jameel, M.; Jumaat, Mohd Zamin; Shirazi, S.M. (International Journal of Physical Sciences, 2011)
Exploration of oil and gas resources has been accelerated towards deeper waters due to depletion of their reserve in shallow water depth. Malaysian sedimentary basins signpost the existence of these energy sources below its sea-bed. In deep sea depth, traditional fixed types of offshore structures to explore these resources have become incongruous and they have resorted to new configurations. Spar platform is treated as a cost-effective and efficient compliant floating platform in this locale for drilling, production, processing and storage of ocean deposits. This study deals with the oil and gas eminence in Malaysian sea along with structural response behaviors of spar platform subjected to hydrodynamic loading. A single model of spar-mooring line combination has been developed. Coupled conduct has been computed under unidirectional wave loading where all non-linearities are incorporated. Solution in time domain approach follows Newmark-beta integration technique. It is seen that the continental shelf offshore of Malaysian waters is divided into seven sedimentary basins, out of which three basins have major ongoing oil and gas exploration and production activity, namely the Malay basin in West Malaysia off Terengganu and the Sabah and Sarawak basins off the two East Malaysian states of Sabah and Sarawak, respectively. Surge, heave, pitch motion response of spar hull and tension in mooring line tension have been evaluated. Spar platform indicates itself as advanced and competent offshore structures to enhance the oil and gas exploration from all the Malaysian sedimentary basins in the deep water region.